1989
DOI: 10.1136/jech.43.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Social class and risk factors for coronary heart disease in the Federal Republic of Germany. Results of the baseline survey of the German Cardiovascular Prevention Study (GCP).

Abstract: The relationship between social class and seven important risk factors for coronary heart disease has been evaluated utilising data from the German Cardiovascular Prevention Study baseline survey. Of German residents aged 25 to 69 years, 16 430 were randomly selected from both the six intervention regions and the Federal Republic of Germany to undergo the screening procedures between 1984 and 1986. Among males the prevalence of cigarette smoking and lack of physical activity was associated with social class. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 11 publications
4
10
1
Order By: Relevance
“…In a study in Norway, age-adjusted mean systolic and diastolic blood pressures were inversely associated with socioeconomic status in women [24]. However, in a study conducted in Germany, the prevalence of hypertension was inversely related to socioeconomic status in women but not in men [25]. Our study found that the relative risk of hypertension was inversely related to socioeconomic status with the exception of education level in women.…”
Section: Discussioncontrasting
confidence: 38%
“…In a study in Norway, age-adjusted mean systolic and diastolic blood pressures were inversely associated with socioeconomic status in women [24]. However, in a study conducted in Germany, the prevalence of hypertension was inversely related to socioeconomic status in women but not in men [25]. Our study found that the relative risk of hypertension was inversely related to socioeconomic status with the exception of education level in women.…”
Section: Discussioncontrasting
confidence: 38%
“…It is difficult to compare our findings regarding overall lifestyle with other studies because few have reported on multiple risk factors and have generally used measures of occupation rather than education [12,28,29,31]. Parental education was not independently associated with having a high healthy lifestyle score.…”
Section: Discussionmentioning
confidence: 66%
“…This was -as expected -a little less than in the large (anonymous) German Cardiovascular Prevention study (Helmert et al 1989). The practice sample showed a similar range as found e. g., in a Dutch study of GPs (Evers et al 1997).…”
Section: Income Out-of-pocket-feesmentioning
confidence: 84%